Investigation of the Effect of Different Facts Devices on Stability in Case of Asymmetric and Symmetrical Fault Condition in Two-Machine System - Turan, Onur; Sari, Yavuz; Koker, Rasit (UIKTEN - ASSOC INFORMATION COMMUNICATION TECHNOLOGY EDUCATION & SCIENCE, 2022)
Many methods have been developed for the control and stability of electrical energy systems. As a result of the researches, more complex systems are produced for electricity generation, transmission and distribution. New modern systems are developed which are capable of changing power flow parameters such as voltage, impedance, power angle, frequency, and power transmission capacity in transmission systems. In this context, the effects of static elements to be connected in parallel or in series to the stability of power system stability studies is one of the most important fields of study of electrical science. In this study, the effects of STATCOM and SVC, one of these shunt flexible AC devices, on the stable operation of the system in case of symmetrical or asymmetric fault situations that may occur in the transmission system are examined in matlab / simulink environment. This study showed that STATCOM provides superior control than SVC and maintains the stability of the system in case of any failure.
Keywords: facts; power system faults; power system stability; power quality; reactive power control; TRANSIENT STABILITY; POWER-SYSTEM; SVC; OPTIMIZATION; OSCILLATION; IMPROVEMENT; STATCOM; Computer Science